The Compositional Effect of Rigorous Teacher Evaluation on Workforce Quality - Julie Berry Cullen; Cory Koedel; Eric Parsons (Center for Economic Studies and ifo Institute (CESifo), 2016)
Improving public sector workforce quality is challenging in sectors such as education where worker productivity is difficult to assess and manager incentives are muted by political and bureaucratic constraints. In this paper, we study how providing information to principals about teacher effectiveness and encouraging them to use the information in personnel decisions affects the composition of teacher turnovers. Our setting is the Houston Independent School District, which recently implemented a rigorous teacher evaluation system. Prior to the new system teacher effectiveness was negatively correlated with district exit and we show that the policy significantly strengthened this relationship, primarily by increasing the relative likelihood of exit for teachers in the bottom quintile of the quality distribution. Low-performing teachers working in low-achieving schools were especially likely to leave. However, despite the success, the implied change to the quality of the workforce overall is too small to have a detectable impact on student achievement.
Keywords: H75; I28; J45; 330; teacher labor market; public sector performance evaluation